2016
DOI: 10.1038/srep35033
|View full text |Cite
|
Sign up to set email alerts
|

PB1 as a potential target for increasing the breadth of T-cell mediated immunity to Influenza A

Abstract: Recently, we showed that combined intranasal and subcutaneous immunization with a non-replicating adenoviral vector expressing NP of influenza A, strain PR8, induced long-standing protection against a range of influenza A viruses. However, H-2b mice challenged with an influenza A strain mutated in the dominant NP366 epitope were not efficiently protected. To address this problem, we envision the use of a cocktail of adenovectors targeting different internal proteins of influenza A virus. Consequently, we inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 24 publications
(33 reference statements)
1
13
0
Order By: Relevance
“…There was also evidence supporting the important protective role of CD8+ T-cell response in human adults upon pandemic H1N1 infection (Sridhar et al, 2013). Notably, unlike the surface viral proteins which evolve fast in response to the pressure of human neutralizing antibodies, the internal IAV structural proteins, as exampled by matrix protein (Fan et al, 2004; Valkenburg et al, 2014), nuclear protein (Lamere et al, 2011; Pica and Palese, 2013), and polymerase protein (Cox and Dewhurst, 2015; Uddback et al, 2016) are more conserved and the derived conserved epitopes have shown potential to induce broad-spectrum cellular responses and provide cross-protection (Jaiswal et al, 2013). It’s also worth mentioning that tissue-resident memory CD8 T cells have been reported to be indispensable for cross-protection against different strains of influenza virus (Brown and Kelso, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…There was also evidence supporting the important protective role of CD8+ T-cell response in human adults upon pandemic H1N1 infection (Sridhar et al, 2013). Notably, unlike the surface viral proteins which evolve fast in response to the pressure of human neutralizing antibodies, the internal IAV structural proteins, as exampled by matrix protein (Fan et al, 2004; Valkenburg et al, 2014), nuclear protein (Lamere et al, 2011; Pica and Palese, 2013), and polymerase protein (Cox and Dewhurst, 2015; Uddback et al, 2016) are more conserved and the derived conserved epitopes have shown potential to induce broad-spectrum cellular responses and provide cross-protection (Jaiswal et al, 2013). It’s also worth mentioning that tissue-resident memory CD8 T cells have been reported to be indispensable for cross-protection against different strains of influenza virus (Brown and Kelso, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Cell-mediated immune responses against highly conserved epitopes in proteins such as the matrix proteins (M1 and M2), the nucleoprotein, and the polymerase basic proteins (PB1 and PB2) have been shown to mediate heterologous and heterosubtypic immunity against influenza A ( 6 , 7 ). Cytotoxic CD8+ T cells are thought to be the primary mediators, but there is mounting evidence that also CD4+ T cells can facilitate of heterologous/-subtypic immunity although the underlying mechanisms are still not completely clear ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although not a major focus for universal influenza virus vaccine development, components of the polymerase, namely PB1, may be of interest for vaccine development, particularly from the standpoint of eliciting heterosubtypic CTLs. One study using non-replicating Ad vectors determined that PB1 was not as immunogenic as NP, but this could be overcome using a molecular adjuvanting approach in which PB1 is fused to the murine invariant chain (Ii), increasing its presentation ( 212 ). This genetic fusion strategy was originally designed to exploit the canonical role of Ii in MHC II presentation, with a view to augmenting Ag presentation to CD4 + T cells, but unexpectedly led to increases in Ag-specific CD8 + T cell responses ( 213 , 214 ).…”
Section: Antigen Targets For Avian Influenza Vaccine Developmentmentioning
confidence: 99%